Analyzing interdisciplinary research team development at the 2024 Kansas Water Institute CoSearch competition - Cori, Sophia Susan Marie (My University, 2025)
Water is inherently interdisciplinary, and it is one of the most urgent and complex challenges for the state of Kansas. Addressing such issues requires collaboration that crosses disciplinary boundaries. In response to this need, Kansas State University’s Kansas Water Institute (KWI) hosted CoSearch, a two-day interdisciplinary research competition focused on the theme of water. The event was designed to catalyze collaboration and accelerate ideation. This study examined how interdisciplinary teams formed during the 2024 KWI CoSearch event. The purpose of this qualitative research was to explore how interdisciplinary collaboration unfolds within a structured event and to identify patterns that influence progress. Guided by Tuckman’s (1965) Stages of Group Development, this study aimed to better understand the dynamics of interdisciplinary collaboration. Semi-structured interviews were conducted with 13 participants from the four teams that competed in KWI’s CoSearch, representing faculty from ten departments across Kansas State University. The interview data were analyzed using open, axial, and selective coding to uncover themes describing how teams evolved and the patterns that supported their progress. Findings revealed evidence of all five of Tuckman’s stages, though development was more fluid than linear. Teams developed and progressed through cycles of Forming, Storming, and Norming as they learned to navigate disciplinary differences and establish shared understanding. By the Performing stage, teams demonstrated cohesion and synergy, enabling high productivity. The Adjourning phase brought divergent outcomes. The winning team continued their research due to seed funding, while others dispersed, highlighting how external incentives influence sustainability. Four unique patterns emerged for the KWI CoSearch teams' interdisciplinary progress: recognition of the value of diverse expertise, ownership of the project, collaboration catalysts, and focused attention. These findings suggest that successful interdisciplinary collaboration depends not only on enthusiasm and shared purpose but also on tangible support and opportunities for sustained engagement. This study contributes to the growing body of literature on interdisciplinary team development and offers practical insights into how structured events like CoSearch can foster collaboration, accelerate innovation, and help institutions of higher education fulfill their interdisciplinary research endeavors.
Keywords: Interdisciplinary collaboration; Team development; Tuckman’s Stages of Group Development; Qualitative research; Higher education; Water research